A 92 F2/ bit Physically Unclonable Function Exploiting Channel Charge Injection and Mismatch Accumulation - Yeo, Injune; Jee, Dong Woo; Seo, Jae Sun (Proceedings of the Custom Integrated Circuits Conference, 2023)
In the deployment of millions of edge devices connected via Internet of Things (loT), each of those devices are exposed as access points for security attacks. As a primitive solution to breaches, physical unclonable functions (PUF) are considered as one of the most cost/energy-efficient approaches providing hardware-oriented randomness, uniqueness, and reliability. PUF can be fundamentally classified into strong and weak PUFs. Strong PUFs can generate a large number of challenge-response pairs (CRPs) according to the given secret. However, due to the correlation between CRPs, it is vulnerable to attacks through the heuristic learning. On the other hand, weak PUFs typically produce a relatively small number of CRPs. Therefore, not only ideal uniqueness and stable response against voltage/temperature variations are important, but also efficient PUF cell area per bit (.F2 / bit) is a critical metric for weak PUFs to produce a large number of CRPs with high density.
Keywords: Access points; Challenge-response pair; Channel charge; Classifieds; Critical metrics; Energy efficient; Heuristic learning; Physically unclonable functions; Security attacks; Temperature variation